STUDI PERILAKU KREDIT BERISIKO MAHASISWA DALAM PENGGUNAAN LAYANAN PAYLATER - Neng Selviana; Zulkarnain (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2025)
This study aims to analyze risky credit behavior among university students, focusing on the use of paylater. This behavior is measured through two main indicators: risky borrowing and risky paying. The study used an online survey distributed to 112 student respondents in Sukabumi. The results show that students in Sukabumi have a significant level of risky credit behavior, with the combined average score for the risky borrowing indicators being 57,44%. This behavior is manifested through a strong tendency to be tempted by discounts (67,68%), make impulsive purchases (54,46%), and use paylater without considering their ability to pay (50,18%). For the risky paying, it was found that for the tendency to be late in making payments was 48,57%, while for ignoring fines reached 50,71%. This indicates that a significant portion of students lack discipline in managing their debt obligations. Further analysis shows a significant difference based on gender, where female have higher scores on almost all risky behavior indicators, such as in impulsive purchases (57,46%) and the tendency to ignore fines (55,87%) compared to males. Therefore, it is suggested that university and financial service providers collaborate to improve students' financial literacy, concerning debt management and the consequences of irresponsible credit behavior.